Efficacy and safety of clozapine combination with different antipsychotics in schizophrenia: a systematic review - Maria Sri Ayu Mustikawati; Bambang Hastha Yoga Legowo Budiman; Zullies Ikawati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Schizophrenia is a severe and chronic mental disorder, where antipsychotics are used as the main therapy. Antipsychotics are commonly used in combination, especially in refractory patients. Clozapine is one of antipsychotics that is often used in combination with other antipsychotic to achieve more effective treatment. However, the effectiveness and safety of the clozapine combination are still inconclusive. This review aimed to evaluate the efficacy and safety evidence of clozapine combination therapy with different other antipsychotics. Relevant articles were collected from Google Scholar, Scopus, and PubMed, and published in 2000-2020. Five studies concerning the effectiveness and safety of clozapine in combination with different other antipsychotics were evaluated. No significant difference in the effectiveness of clozapine in combination with other antipsychotics was observed in 4 studies. No significant difference in the safety of all clozapine combinations was observed in 3 studies. Only 2 studies reported that the clozapine-atypical antipsychotic combination (clozapine-aripiprazole) is more tolerable compared to the clozapine-typical antipsychotic. In conclusion, the efficacy and safety of clozapine in combination with different other antipsychotics have not been definitively conclusive, yet.